2012
DOI: 10.1177/0022034512443367
|View full text |Cite
|
Sign up to set email alerts
|

Suberoylanilide Hydroxamic Acid Enhances Odontoblast Differentiation

Abstract: Previous studies have shown that histone deacetylase (HDAC) inhibitors stimulate osteoblast differentiation in vitro and bone formation in vivo. However, the effects of HDAC inhibitors on odontoblasts have not been elucidated. Therefore, in this study, we examined the effect of suberoylanilide hydroxamic acid (SAHA), an HDAC inhibitor, on odontoblast differentiation using an MDPC23 odontoblast-like cell line. SAHA significantly enhanced matrix mineralization and the expression levels of odontoblast marker gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 25 publications
5
36
0
Order By: Relevance
“…Accompanying significant increased transcription of the mineralization-associated genes, transforming growth factor beta-1 (TGF-b1), bone morphogenetic protein-4 (BMP-4) and the dentinogenic transcript DMP-1 were noted, leading to the conclusion that HDACi can epigenetically modulate the cell enabling acceleration of mineralization and odontoblast-like cell differentiation. These results were further corroborated with the same cell line using a different HDACi (SAHA), which also enhanced matrix mineralization and the expression levels of the odontoblast differentiation markers nuclear factor I/C (Nfic) and DSPP as well as increasing the acetylation of the core histone H3 (Kwon et al 2012). Furthermore, it was demonstrated that Nfic bound directly to the DSPP promoter and stimulated DSPP transcription suggesting a possible mechanism by which SAHA promoted odontogenic events.…”
Section: Differentiationsupporting
confidence: 56%
See 2 more Smart Citations
“…Accompanying significant increased transcription of the mineralization-associated genes, transforming growth factor beta-1 (TGF-b1), bone morphogenetic protein-4 (BMP-4) and the dentinogenic transcript DMP-1 were noted, leading to the conclusion that HDACi can epigenetically modulate the cell enabling acceleration of mineralization and odontoblast-like cell differentiation. These results were further corroborated with the same cell line using a different HDACi (SAHA), which also enhanced matrix mineralization and the expression levels of the odontoblast differentiation markers nuclear factor I/C (Nfic) and DSPP as well as increasing the acetylation of the core histone H3 (Kwon et al 2012). Furthermore, it was demonstrated that Nfic bound directly to the DSPP promoter and stimulated DSPP transcription suggesting a possible mechanism by which SAHA promoted odontogenic events.…”
Section: Differentiationsupporting
confidence: 56%
“…These results were further corroborated with the same cell line using a different HDACi (SAHA), which also enhanced matrix mineralization and the expression levels of the odontoblast differentiation markers nuclear factor I/C (Nfic) and DSPP as well as increasing the acetylation of the core histone H3 (Kwon et al . ). Furthermore, it was demonstrated that Nfic bound directly to the DSPP promoter and stimulated DSPP transcription suggesting a possible mechanism by which SAHA promoted odontogenic events.…”
Section: Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Next, we investigated whether the Cpne7-Nucleolin complex binds specifically to the Dspp promoter. A positive control was designed using the well-characterized nuclear factor IeC antibody on DSPP promoter [28]. Chromatin immunoprecipitation (ChIP) assay revealed that Nucleolin bound to the Dspp promoter, whereas negative control (pre-immune serum) or Nucleolin siRNA did not precipitate the Dspp promoter fragment (Fig.…”
Section: Cpne7 Interacts With Nucleolin and Regulates Odontoblast Difmentioning
confidence: 99%
“…Disruption of the Nfic gene in mice leads to abnormal tooth roots that are predominantly caused by abnormal odontoblast differentiation and dentin formation during root formation (5-7). Previously, we suggested that Nfic transcriptionally activates DSPP expression (8).…”
mentioning
confidence: 96%